2020
DOI: 10.1021/acs.inorgchem.9b03200
|View full text |Cite|
|
Sign up to set email alerts
|

Nearly Identical but Not Isotypic: Influence of Lanthanide Contraction on Cs2NaLn(PS4)2 (Ln = La–Nd, Sm, and Gd–Ho)

Abstract: The effect of lanthanide contraction often results in topological and symmetry changes in compounds with the same compositions as a function of lanthanide cation size. Here we report on the first example of a lanthanide thiophosphate exhibiting a change in the lanthanide cation environment without any topological or symmetry change. A series of new lanthanide thiophosphates with mixed alkali cations were obtained via a flux crystal growth technique using a CsI flux. The obtained compounds Cs2NaLn­(PS4)2 (Ln = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 89 publications
2
10
0
Order By: Relevance
“…In this study, we observed that on moving across the lanthanide series (Eu–Lu), the symmetry of the compounds changes and the coordination number of the lanthanide cations decreases from 9 to 8, as a consequence of lanthanide contraction, resulting in six different compositions. By comparison, this effect was observed by Klepov et al where a minor change in size between the lanthanide cations causes a sharp change in the coordination environment and coordination number, resulting in different structure types . The lanthanide chloride compounds, although having different symmetries and compositions, all consist of lanthanide polyhedra that are isolated from each other but linked into a complex structure by Cs–Cl/Cs–O bonds and by extensive OH–O hydrogen bonding and OH–Cl interactions.…”
Section: Results and Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, we observed that on moving across the lanthanide series (Eu–Lu), the symmetry of the compounds changes and the coordination number of the lanthanide cations decreases from 9 to 8, as a consequence of lanthanide contraction, resulting in six different compositions. By comparison, this effect was observed by Klepov et al where a minor change in size between the lanthanide cations causes a sharp change in the coordination environment and coordination number, resulting in different structure types . The lanthanide chloride compounds, although having different symmetries and compositions, all consist of lanthanide polyhedra that are isolated from each other but linked into a complex structure by Cs–Cl/Cs–O bonds and by extensive OH–O hydrogen bonding and OH–Cl interactions.…”
Section: Results and Discussionmentioning
confidence: 79%
“…By comparison, this effect was observed by Klepov et al where a minor change in size between the lanthanide cations causes a sharp change in the coordination environment and coordination number, resulting in different structure types. 43 The lanthanide chloride compounds, although having different symmetries and compositions, all consist of lanthanide polyhedra that are isolated from each other but linked 5)°f orming a distorted square antiprism (Figure 2a). The Cs1− Cs2, Cl1−Cl7, and O1−O6 are located at positions of general crystallographic symmetry (Wyckoff site 8d), whereas Cs3− Cs8, Cl8−Cl10, and O7−O9 are located on or are disordered across (O9) mirror planes (Figure S3).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The new lithium-containing lanthanum(III) ortho-thiophosphate(V) Li 3 La[PS 4 ] 2 crystallizes orthorhombically in the space group Pbca (no. 61) displaying the lattice parameters a = 1053.51(6) pm, b = 1920.62 (11) pm and c = 1165.83 (7) pm with Z = 8 (Table 1). There is only one crystallographically unique lanthanum position, three lithium, two phosphorus and eight sulfur sites, all located on the general Wyckoff position 8c, within the crystal structure of Li 3 La[PS 4 ] 2 (Table 2).…”
Section: Crystal Structure Of LI 3 La[ps 4 ]mentioning
confidence: 99%
“…Alkali-metal containing lanthanoid(III) ortho-thiophosphates(V) occur with a rich variety of compositions, for example K 9 Ce-[PS 4 ] 4 , [1] K 3 Ce[PS 4 ] 2 , [2] K 6 Yb 3 [PS 4 ] 5 , [3] K 3 Nd 3 [PS 4 ] 4 , [4] Rb 3 Sm[PS 4 ] 2 , [5] Rb 3 Pr 3 [PS 4 ] 4 , [6] Cs 3 Sm[PS 4 ] 2 , [5] Cs 3 Nd[PS 4 ] 2 , [4] Cs 3 La 5 [PS 4 ] 6 [7] and Cs 3 Pr 5 [PS 4 ] 6 , [8] especially when the heavy representatives potassium, rubidium and cesium are considered. In their crystal structures the discrete [PS 4 ] 3À tetrahedra do not only provide coordination spheres with mostly eight sulfur atoms to the central Ln 3 + cations, as it is also the case for the ternary Ln[PS 4 ] phases (Ln = LaÀ Yb [9,10,11,12] except for Lu [13] with C.N.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation